2011
DOI: 10.1371/journal.pone.0026367
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Thrombin in Complex with S-Variegin: Insights of a Novel Mechanism of Inhibition and Design of Tunable Thrombin Inhibitors

Abstract: The inhibition of thrombin is one of the important treatments of pathological blood clot formation. Variegin, isolated from the tropical bont tick, is a novel molecule exhibiting a unique ‘two-modes’ inhibitory property on thrombin active site (competitive before cleavage, noncompetitive after cleavage). For the better understanding of its function, we have determined the crystal structure of the human α-thrombin:synthetic-variegin complex at 2.4 Å resolution. The structure reveals a new mechanism of thrombin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 59 publications
2
53
0
Order By: Relevance
“…Investigations have included studies on anti‐tumoral effects (Chudzinski‐Tavassi et al ., 2010; Abreu et al ., 2014; Sousa et al ., 2015), applications against inflammatory diseases like myasthenia gravis (Hepburn et al ., 2007), new anticoagulants (Koh et al ., 2011) and the treatment of asthma (Horka et al ., 2012). …”
Section: Tick Saliva As a Source Of Toxins Tick‐borne Pathogens And mentioning
confidence: 99%
“…Investigations have included studies on anti‐tumoral effects (Chudzinski‐Tavassi et al ., 2010; Abreu et al ., 2014; Sousa et al ., 2015), applications against inflammatory diseases like myasthenia gravis (Hepburn et al ., 2007), new anticoagulants (Koh et al ., 2011) and the treatment of asthma (Horka et al ., 2012). …”
Section: Tick Saliva As a Source Of Toxins Tick‐borne Pathogens And mentioning
confidence: 99%
“…Another distinctive feature of madanins is the absence of cysteine residues in their amino acid sequence, placing them in the restricted group of cysteine-less thrombin inhibitors, together with thrombostasin (from the horn fly Haematobia irritans [10]; MEROPS family I64), tsetse thrombin inhibitor (from Glossina morsitans morsitans [11]; MEROPS family I76), chimadanin (from H. longicornis [12]; MEROPS family I72), anophelin (from Anopheles mosquitoes [13]; MEROPS family I77) and variegin (from the tropical bont tick Amblyomma variegatum [14]; MEROPS family I74). The molecular mechanism of action of two of these atypical serine proteinase inhibitors, anophelin and variegin, has been unveiled by the crystallographic three-dimensional structures of their complexes with thrombin [15], [16]. Whereas anophelin and variegin bind tightly to thrombin, madanins were shown to bind to thrombin with low affinity [7].…”
Section: Introductionmentioning
confidence: 99%
“…Thrombin is an atypical (chymo)trypsin-like enzyme, with stringent specificity arising from its narrow active site cleft and secondary positively charged recognition surfaces (exosites) (12). Exosites are not only essential for substrate and cofactor binding (13)(14)(15)(16)(17)(18) but also, are targeted by many natural anticoagulants (19)(20)(21)(22)(23)(24)(25). Thorough kinetic analyses revealed that anophelin is a dual inhibitor that binds both the exosite I and the active site of the target proteinase (6,7).…”
mentioning
confidence: 99%